DEVELOPING ENGLISH SPEAKING MATERIALS FOR STUDENTS OF OFFICE ADMINISTRATION PROGRAM OF VOCATIONAL SCHOOL - Dumora Malina Sijabat and Sortha Silitonga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
The objective of this study was to develop English speaking materials based on students’ needs. This study followed the steps of research and development proposed by Borg and Gall, which are 1) need analysis; 2) planning(writing syllabus); 3) designing materials; 4) material evaluation; 5) revising (writing final product). It was found that 82.85% students agreed that the existing materials currently used by the students were irrelevant with office administration program. The more relevant materials were then developed based on scientific approach and relevant with their study program and work life situation. The learning materials were developed into 3 units of speaking materials. The learning materials were then validated by two experts. The average score of the validation was 85. It showed that the developed learning materials were very good, relevant and feasible.